The first resolution revolution in protein structure analysis: X-ray diffraction of polypeptide conformations and globular protein folds in 1950s and 1960s - Blundell, Tom L. (Progress in biophysics and molecular biology, 2021)
Although determination of structures of biological molecules became a real possibility after the first X-ray analyses of crystals by the William Henry Bragg and his son Lawrence in 1913, the crystal structure determination of globular proteins became a possibility only in 1934 with the demonstration of X-ray diffraction from pepsin by J D Bernal and Dorothy Crowfoot, later Hodgkin, who had realised the importance of maintaining an aqueous environment for proteins in crystals. After a further 20 years of hard work by Max Perutz, John Kendrew and others the structures of haemoglobin and myoglobin emerged. Further innovation resulted in a revolution in X-ray diffraction studies in the 1960s, which focused first on polypeptides with alpha helix, beta strand and collagen polyproline helix structures, described in a review by David Davies in 1965 in the journal Progress in Biophysics, later to become Progress in Biophysics and Molecular Biology. It was followed in 1969 by a further detailed review by Tony North and David Phillips in the same journal on crystal structure a nalyses of globular proteins that successfully emerged soon after that of myoglobin. These included the structure of the first enzyme, lysozyme, followed by structures of chymotrypsin, trypsin, carboxypeptidase and many others. This first resolution revolution in X-ray analysis described in the two reviews is the subject of this retrospective analysis just over five decades later.